ESTIMATION OF SOME METALS IN WORKER OF DYES INDUSTRIES - Ahmed, Rafah Kh (Al-Nahrain Journal of Science, 2009)
This study involve in an estimation of some metals in sera of workers in one of the dyes industries in Baghdad city, the content of blood serum from lead, copper and zinc were analyzed in twenty two sera samples of workers using the Atomic Absorption Spectroscopy (AAS) instrument type (AAS VARID 6 Analytik Jena AG), also, twenty two sera samples were used as a control cases in this study .It was found that the zinc concentrations were decreased in the sera of workers who worked in the dyes industry compared to control cases, but increased in the levels of both two elements lead and copper in the sera of workers compared with the control cases.